A Conceptual Study on Hridayavarnaka Karma of Gairika w.s.r to Hridroga (International Journal of Ayurveda and Pharma Research, 2023)
Hridaya is the entity in the body which acts as a central beam that supports the framework of the body system. Gairika is a Uparasa Dravya. In twenty-four Vishopakrama, Hridayavarana is said to be done daily. The primary duty of the physician is to protect the heart. Hridayavarana refers to measures used to create a protective covering around the heart. Gairika is a Hridayavarana Dravya. An effort was made to collect references pertaining to Hridaya, Hridroga Hridayavarana and Gairika across Ayurveda texts like Charaka Samhita, Rasaratna Samucchaya etc. Hridaya is an important organ characterized as Siraja Sadhyopranahara Marma as well as one among the Pranayama. Any condition which manifests as a discomfort to heart is termed Hridroga. These terms Hridya conveys the notion of something that is favourable or beneficial for the heart. Gairika is a Parthiva Dravya classified in group of Bhoumadravya, Shonitastapana Deshamani, Uparasa, Suvarnadi and Upadhatu of Loha. Gunas of Gairika include Madhura rasa, Snigdha and Laghu Guna Tapahara, Sheeta veerya, Balya, Ropana, Raktashodhaka, Pittanashaka. It is indicated for Raktapitta, Daha, Chardhi, Vishahara, Hikka, Asungdhara, Netraroga, Udarda, Kandu, Vrana, Jwara. The Subhavita Shuddha Gairika is a Prashasta Bheshaja for Hridayavarana Upakrama on its qualities of being safe, effective and abundance.